Perceived emotional distress and fear of Covid-19 among young adults during pandemic - Khurram, Fatima; Fahd, Samar; Waseem, Aqsa; Firdos, Sajida; Kaleem, Hina (Journal of Pakistan Psychiatric Society, 2021)
OBJECTIVE To examine the relationship of perceived emotional distress and fear of COVID-19 among young adults and to check the difference among gender and marital status in perception of emotional distress and fear of COVID-19. STUDY DESIGN Cross-sectional research design. PLACE AND DURATION OF THE STUDY The data was collected from city Bahawalpur, Punjab, Pakistan during September 2020 to February 2021. SUBJECTS AND METHODS Participants were 200 educated, married and unmarried young adults of both genders, two scales were used in the study to collect data, Perceived Emotional Distress Inventory (PEDI) and The Fear of COVID-19 Scale along with self-structured demographic sheet. RESULTS Results revealed that the fear of COVID-19 and perceived emotional distress are significantly correlated with each other. Fear of COVID-19 and perceived emotional distress is higher among females as compare to males. Perceived emotional distress is higher among married people as compare to unmarried ones but fear of COVID-19 is not significantly different among marital status. CONCLUSION It is concluded that fear of COVID-19 can strongly relate to perceived emotional distress and both of them persist more among females. There is no discrimination of marital status in perception of fear of COVID-19, but emotional distress does occur more among married individuals.